Does Latin American and Caribbean Unemployment Depend on Asian Labor Standards? - Patrick Belser (Inter-American Development Bank, Office of the Chief Economist, 1998)
Many Latin American nations have recently implemented liberal trade regimes, often as part of a larger set of market-oriented reforms, and have abandoned their industrialization policies based on import substitution. In the 1980s, Chile, Mexico, and Bolivia were among the continent`s first nations to slash tariff rates and virtually eliminate quantitative restrictions on imports. They were followed by many others, including Argentina, Brazil, Colombia, Jamaica, Peru, Uruguay, Venezuela, and Trinidad and Tobago. All these countries are now much more exposed to international competition than ever before. But is this a good idea? Are labor rights really more restricted in export-oriented Asian nations than they are in Latin America? And if so, are Latin American workers prejudiced by Asia`s lower standards?
Keywords: 330